The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.9738/intsurg-d-14-00100.1
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Carcinoembryonic Antigen and Prognosis of Colorectal Cancer. An Independent Prognostic Factor Still Reliable

Abstract: To evaluate whether, in a sample of patients radically treated for colorectal carcinoma, the preoperative determination of the carcinoembryonic antigen (p-CEA) may have a prognostic value and constitute an independent risk factor in relation to disease-free survival. The preoperative CEA seems to be related both to the staging of colorectal neoplasia and to the patient's prognosis, although this-to date-has not been conclusively demonstrated and is still a matter of intense debate in the scientific community. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 38 publications
1
12
0
1
Order By: Relevance
“…Our results demonstrated that the CEA and CA 19-9 levels were higher compared with the normal values. CEA correlates with disease-free survival after surgery for CRC (23). These results and previous reports suggest that CRC diagnosed with abdominal US is advanced.…”
Section: ) ------------------------------------------------------supporting
confidence: 82%
“…Our results demonstrated that the CEA and CA 19-9 levels were higher compared with the normal values. CEA correlates with disease-free survival after surgery for CRC (23). These results and previous reports suggest that CRC diagnosed with abdominal US is advanced.…”
Section: ) ------------------------------------------------------supporting
confidence: 82%
“…Many studies have supported the prognostic value of preoperative CEA levels. 133 Park et al 134 analyzed 2,230 CRC patients and found that CEA level was significantly associated with patient outcomes. According to 2 large-scale case studies, preoperative CEA level was significantly associated with prognosis in patients with CRC that metastasized to the liver.…”
Section: Blood Biomarkers 1) Cea Levelsmentioning
confidence: 99%
“…This is in contrast to larger studies including that of Destri et al . who studied 395 patients with colorectal cancer and found that a pre‐operative CEA above 5 ng/mL was associated with a significantly increased risk of recurrence (OR 1.02, P = 0.004) . Patients in the present study dying from undetected recurrent disease may explain the difference in DFS between high and low CEA patients and would require autopsy data to explore this further.…”
Section: Discussionmentioning
confidence: 67%